Preparing Silver Linings for a Cloudy Day: The Consequences of Preemptive Benefit Finding. (August 2022) - Rankin, Kyla; Sweeny, Kate
Waiting for important news is stressful. In four studies, we assess the utility of preemptive benefit finding, a coping strategy in which people seek silver linings in bad news before receiving news, for emotional well-being across several waiting periods (waiting for bar exam results, the outcome of political elections, and results of a fictitious health risk assessment). Our findings support the effectiveness of preemptive benefit finding while waiting, such that identifying benefits in bad news while waiting predicts more positive emotions during the wait (Studies 3 and 4) and buffers people against the emotional consequences of bad news by boosting post-news positive emotions (Studies 2–4). Importantly, engaging in preemptive benefit finding does not backfire if a person ultimately receives good news (Studies 1, 3, and 4). We discuss results from a mini meta-analysis and consider implications of our findings for interventions to improve well-being while waiting and after news arrives.